PENGEMBANGAN PROTOKOL TRANSITIONAL CARE DI RUANG RAWAT INAP KARDIOVASKULER RSUP H. ADAM MALIK MEDAN - Ance M Siallagan (Elisabeth Health Jurnal, 2019)
The transitional care protocol is a guide developed as a guide in applying transitional care for patients with congestive heart failure from hospital to home to prevent early readmissions. Goals:This study aims to develop transitional care protocols in Cardiovascular Inpatient Ward at Hospital in Medan. Methods: Action research through two cycles consisting of reconnaissance, planning, action, observation, and reflection used to collect data. Participants consisted of 17 nurses in the cardiovascular ward. Data were analyzed through content analysis and descriptive statistic test. Results: The result of this research was transitional care protocol consist of screening patients at risk of readmissions, patient and family involvement, promoting self management, identification of symptoms and how to overcome them, and nurse collaboration with other health worker in the hospital. Observation results showed that 70.58% of participants were able to do transitional care. increased of nurses' knowledge of transitional care and patient's ready to continuity of care at home. Conclusion: The hospital should monitor and evaluate the implementation of the transitional care protocol and become one of the indicators of the assessment of nurse's performance